NETs and CF Lung Disease: Current Status and Future Prospects - Gray, Robert D. (Antibiotics (Basel), 2015)
Cystic Fibrosis (CF) is the most common fatal monogenic disease among Caucasians. While CF affects multiple organ systems, the principle morbidity arises from progressive destruction of lung architecture due to chronic bacterial infection and inflammation. It is characterized by an innate immune defect that results in colonization of the airways with bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa from an early age. Within the airway microenvironment the innate immune cells including epithelial cells, neutrophils, and macrophages have all been implicated in the host defense defect. The neutrophil, however, is the principal effector cell facilitating bacterial killing, but also participates in lung damage. This is evidenced by a disproportionately elevated neutrophil burden in the airways and increased neutrophil products capable of tissue degradation, such as neutrophil elastase. The CF airways also contain an abundance of nuclear material that may be originating from neutrophils. Neutrophil extracellular traps (NETs) are the product of a novel neutrophil death process that involves the expulsion of nuclear material embedded with histones, proteases, and antimicrobial proteins and peptides. NETs have been postulated to contribute to the bacterial killing capacity of neutrophils, however they also function as a source of proteases and other neutrophil products that may contribute to lung injury. Targeting nuclear material with inhaled DNase therapy improves lung function and reduces exacerbations in CF and some of these effects may be due to the degradation of NETs. We critically discuss the evidence for an antimicrobial function of NETs and their potential to cause lung damage and inflammation. We propose that CF animal models that recapitulate the human CF phenotype such as the CFTR(−/−) pig may be useful in further elucidating a role for NETs.